The measurement and evaluation of library services, de Frederic Wilfred Lancaster (Revista de Biblioteconomia de Brasília, 1980)
LANCASTER, Frederic Wilfred. The measurement and evaluation of library services. Washington D.C.: Information Resources Press, 1977. 395 p.